Implementasi SPK SAW Untuk Analisis Kepuasan Pelanggan Rumah Makan Padang - Gusriva, Revi; Sentosa, Rio Bayu; Randa, Dimas Dwi (LPPM STIKOM Tunas Bangsa, 2024)
Customer satisfaction is an important aspect that determines the success of a business, including restaurants. In order to improve service quality, a system is needed that is able to analyze customer satisfaction levels effectively. This research aims to implement the Simple Additive Weighting (SAW) method in a decision-making system to evaluate and analyze customer satisfaction at Padang Restaurants. The SAW method was chosen because of its ability to provide assessments based on predetermined criteria and weights so that each value of the sum of the weights of the results obtained will be the final decision. This system uses several main criteria, such as food quality, cleanliness, service, price and atmosphere of the place. Input data in the form of customer assessments against each criterion is processed using the SAW method to produce satisfaction level ratings. The research results show that this system is able to provide accurate analysis results and assist restaurant management in making strategic decisions to improve service. Thus, implementing the SAW method in customer satisfaction analysis can be an effective solution in supporting quality management in the culinary industry. The final result was that the highest score was obtained from customer III with a value of 1, customer 2 with a value of 0.84 and customer III obtained a value of 0.7025.